Advanced Analytical Treatment of Fractional Logistic Equations Based on Residual Error Functions. (25th September 2019) - Alshammari, Saleh; Al-Smadi, Mohammed; Al Shammari, Mohammad; Hashim, Ishak; Alias, Mohd Almie
Abstract : In this article, an analytical reliable treatment based on the concept of residual error functions is employed to address the series solution of the differential logistic system in the fractional sense. The proposed technique is a combination of the generalized Taylor series and minimizing the residual error function. The solution methodology depends on the generation of a fractional expansion in an effective convergence formula, as well as on the optimization of truncated errors, Res q j t, through the use of repeated Caputo derivatives without any restrictive assumptions of system nature. To achieve this, some logistic patterns are tested to demonstrate the reliability and applicability of the suggested approach. Numerical comparison depicts that the proposed technique has high accuracy and less computational effect and is more efficient.